How to Fund Unemployment Insurance with Informality and False Claims: Evidence from Senegal - Abdoulaye Ndiaye; Kyle Herkenhoff; Abdoulaye Cissé; Alessandro Dell'Acqua; Ahmadou A. Mbaye (CESifo GmbH, 2024)
This paper studies the welfare effects associated with the provision of unemployment insurance (UI) benefits when formal workers represent only a small proportion of the labor market and informal workers can submit fraudulent claims for UI benefits. We develop a model that incorporates these features and also allows for varying degrees of enforcement and funding sources. We then estimate the model's key parameters by conducting a custom labor force survey in Senegal. We show that the moral hazard response to the UI benefits among workers is small and their liquidity gains are large: an extra dollar of UI benefits yields a consumption-equivalent gain of 50–80 cents, which exceeds comparable U.S. estimates by a factor of 10–20. We then show that the welfare gains depend on the program design: UI funded through payroll taxes is effective and feasible as long as the ratio of formal workers to the benefit level is sufficiently high, while UI funded through consumption taxes generally offers lower welfare benefits but is more resistant to fraudulent claims. Our study highlights the welfare importance of the design of UI financing and suggests large liquidity and consumption smoothing gains of UI in contexts with high informality and potential fraud.
Keywords: 330; Arbeitslosenversicherung; Informelle Wirtschaft; Friktionelle Arbeitslosigkeit; Wohlfahrtsanalyse; Senegal